IMPACT OF RADIATION AND CHEMORADIATION WITH MITOMYCIN-C ON CELLULAR IMMUNITY OF PATIENTS WITH LOCALLY ADVANCED CERVICAL CANCER - BADRI, Cholid (The ASEAN Journal of Radiology, 2023)
OBJECTIVE: To evaluate the impact of chemoradiation therapy with Mitomycin-C (MMC) on the cellular immunity of patients with locally advanced cervical cancer compared with radiation therapy alone. MATERIALS AND METHODS: Fifty-six patients with locally advanced cervical cancer were divided into two groups, 34 patients treated with radiation alone and 22 patients with chemoradiation. Chemoradiation was performed by adding 15 mg MMC/ m? body surface through intravenous bolus injection on the first day of external radiation and on the first day of intracavitary radiation during the radiation routinely administered. In all patients, lymphocyte transformation test was performed after completion of external radiation, in one month, and three months after full-course treatment. RESULTS: In radiation group, a significant decrease of lymphocyte transformation index was evident after external radiation compared with pre-treatment values, i.e., from 25.82 + 14.30 % to 19.02 + 10.54 % (p = 0.08). These parameters were further decreased to 17.85 + 9.63 % in one month after full-course radiation. Although there was an increase to 18.97 + 9.29 % at three months after full-course radiation, these values were still significantly lower than the values before radiation (p = 0.015). In chemoradiation group, there was an insignificant decrease of lymphocyte transformation index after external radiation and first MMC administration, compared with the values before radiation, i.e., 19.09 + 12.66 % to 21.72 + 12.68 %. A significant decrease of these parameters to 13.68 + 8.23 % (p= 0.038) was noted at one month after fullcourse chemoradiation compared with the values before treatment. There was an increase of the parameters to 17.31 + 11.32 % after full-course chemoradiation, such that they were not significantly different from the values before treatment. CONCLUSIONS: Chemoradiation with MMC in patients with locally advanced cervical cancer did not result in greater impact on cellular immunity than radiation alone; the parameters would even improve rapidly in three months after treatment. The factors that possibly played a part in such condition were working mechanism and interval of MMC administration, as well as rebounded overshoot phenomena of lymphocyte transformation after cytotoxic treatment.